Better skills, better jobs, better lives. A strategic approach to skills policies (Paris, 2012)
"Recognising both the complexity of skills policies and the potential for peer learning, the OECD has developed a global Skills Strategy that helps countries to identify the strengths and weaknesses of their national skills systems, benchmark them internationally, and develop policies that can transform better skills into better jobs, economic growth and social inclusion. This book presents a strategy that will help countries reach the goal of having and making the best use of a high-quality pool of skills. The OECD Skills Strategy shifts the focus from traditional measures of skills, such as years of initial education and training or qualifications attained, to a much broader perspective that includes the skills people can acquire, use and maintain–and also lose–over a whole lifetime. Without sufficient investment in skills, people languish on the margins of society, technological progress does not translate into economic growth, and countries can no longer compete in an increasingly knowledge-based global society. In addition, the book points out that for skills to retain their value, they must be continuously maintained and upgraded throughout life so that people can collaborate, compete and connect in ways that drive economies and societies forward."